The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/jiabr-05-2021-0145
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the impact of productive zakat on the welfare of zakat recipients

Abstract: Purpose This study aims to investigate the effects of zakat and business assistance on the growth and well-being of mustahiqs (zakat recipients). This study also investigates the impact of macroeconomic variables on the welfare of mutahiqs. Design/methodology/approach The partial least squares-structural equation modelling method is used in this quantitative study, examining data from 137 mustahiqs. The data was collected from seven zakat institutions, which run effective zakat programmes to empower mustahiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 68 publications
2
16
0
4
Order By: Relevance
“…Several research findings have uncovered the role of zakat during the COVID-19 pandemic. Mawardi et al (2022) found that productive zakat can increase business income for mustahik who own a business even during the COVID-19 pandemic. This shows that the productive zakat funds that are channeled to mustahik make mustahik able to survive in business even in global economic conditions that are experiencing a decline.…”
Section: Resultsmentioning
confidence: 99%
“…Several research findings have uncovered the role of zakat during the COVID-19 pandemic. Mawardi et al (2022) found that productive zakat can increase business income for mustahik who own a business even during the COVID-19 pandemic. This shows that the productive zakat funds that are channeled to mustahik make mustahik able to survive in business even in global economic conditions that are experiencing a decline.…”
Section: Resultsmentioning
confidence: 99%
“…This complex multivariate regression method (Hair et al , 2019) explains and reveals a relationship between variables (Sinkovics et al , 2016). PLS-SEM can be used when the distributional assumptions cannot be met (Mawardi et al , 2022; Widiastuti et al , 2021). The philosophy of using the PLS-SEM method is for research to predict and develop theory.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of zakat as productive zakat encourages efforts to work optimally and obtain decent outcomes. On the other hand, the economic situation of mustahik or zakat empowerment programme recipients is not too influenced by macroeconomic variables that show the economic resilience of the lower layers (Mawardi et al, 2022).…”
Section: Analysis Of the Business Development Of Productive Zakat Rec...mentioning
confidence: 99%